(08.03)A set of equations is given below:

Equation H: y = −x + 2
Equation J: y = 3x − 4

Which of the following steps can be used to find the solution to the set of equations?
−x = 3x − 4
−x +2 = 3x
−x + 2 = 3x − 4
−x + 1 = 3x + 2

Respuesta :

Answer: Third option

[tex]-x + 2 = 3x - 4.[/tex]

Step-by-step explanation:

One of the ways of solving a system of equations is by equating the equations and solving for one of the variables.

In this case we have the system:

[tex]y = -x + 2\\\\y = 3x - 4[/tex]

Note that if [tex]y[/tex] is equal [tex]-x + 2[/tex] and also [tex]y[/tex] equals [tex]3x - 4[/tex]

Then logically [tex]-x + 2[/tex] must be equal to [tex]3x - 4[/tex].

We write equality.

[tex]-x + 2 = 3x - 4.[/tex]

Then the correct answer is the third option.

We can also solve for the variable x

[tex]-4x = -6\\\\4x = 6\\\\x = \frac{6}{4}\\\\x = \frac{3}{2}[/tex]